Gonococcal Infection and Ventriculoperitoneal Shunts. Issue 12 (6th December 2022) - Freeman, Megan Culler; Lazzara, Alexandra; Lennon, Tyler; McAteer, John; Pease, Matthew; Sefcik, Roberta; Radovic-Stakic, Ana; Milstone, Aaron M.; Nowalk, Andrew; Trent, Maria
Abstract : This case report describes two adolescent patients with ventriculoperitoneal shunt infection with Neisseria gonorrhoea e. Abstract: Neisseria gonorrhoea e and Chlamydia trachomatis are pathogens commonly isolated in pelvic inflammatory disease. Neisseria gonorrhoea e may uncommonly spread outside the urogenital tract to cause complications. We present 2 cases of adolescents with ventriculoperitoneal shunt infection due to N. gonorrhoea e, requiring shunt externalization.